An active-learning based training-schedule for biomedical image segmentation on deep neural networks - Hassan, Mehadi; Das, Shemonto; Dipu, Shoaib Ahmed (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.